Protein tyrosine phosphatases in health and disease. (1st October 2012) - Hendriks, Wiljan J. A. J.; Elson, Ari; Harroch, Sheila; Pulido, Rafael; Stoker, Andrew; den Hertog, Jeroen
<x xml:space="preserve">Abstract</x> Protein tyrosine phosphatases (PTPs) represent a super‐family of enzymes that play essential roles in normal development and physiology. In this review, we will discuss the PTPs that have a causative role in hereditary diseases in humans. In addition, recent progress in the development and analysis of animal models expressing mutant PTPs will be presented. The impact of PTP signaling on health and disease will be exemplified for the fields of bone development, synaptogenesis and central nervous system diseases. Collectively, research on PTPs since the late 1980's yielded the cogent view that development of PTP‐directed therapeutic tools is essential to further combat human disease.